Influence of temperature on the respiratory rate of Nile Tilapia, Oreochromis niloticus (Pisces: Cichlidae) in the laboratory (UNED Research Journal, 2016)
Tilapia, Oreochromis niloticus, (Linneaus, 1758) is an important aquaculture species in Nigeria and other parts of the world. We obtained specimens (3,5-13,00 cm total length; 1,7 to 49 g) from Jabi Reservoir, Nigeria, and exposed them to 18-38o C. The frequency of opercular beats (i.e.respiratory rate) was determined from videos. At room temperature (28o C), the average frequency of opercular beats per minute for the weight groups of 1, 7 – 3,3; 4,0 – 7,0; 11,0 – 20 and 40 – 49g were 218, 190, 167 and 119 respectively. It decreased to 153, 137, 94 and 77 beats respectively when the water temperature was lowered to 18o C. It subsequently increased to 283, 267, 209 and 136 beats respectively when water temperature was raised to 38o C (p
Keywords: Temperature; Respiratory rate; Oreochromis niloticus; Laboratory